Inflammation‐ and angiogenesis‐related biomarkers are correlated with cancer‐related fatigue in colorectal cancer patients: Results from the ColoCare Study. (24th April 2019) - Himbert, Caroline; Ose, Jennifer; Lin, Tengda; Warby, Christy A.; Gigic, Biljana; Steindorf, Karen; Schrotz‐King, Petra; Abbenhardt‐Martin, Clare; Zielske, Lin; Boehm, Juergen; Ulrich, Cornelia M.
Abstract: Cancer‐related fatigue is one of the most common side effects of colorectal cancer treatment and is affected by biomedical factors. We investigated the association of inflammation‐ and angiogenesis‐related biomarkers with cancer‐related fatigue. Pre‐surgery (baseline) serum samples were obtained from n = 236 newly diagnosed colorectal cancer patients. Meso Scale Discovery assays were performed to measure levels of biomarkers for inflammation and angiogenesis (CRP, SAA, IL‐6, IL‐8, MCP‐1, sICAM‐1, sVCAM‐1, TNFα, VEGFA and VEGFD). Cancer‐related fatigue was assessed with the EORTC QLQ‐30 questionnaire at baseline and 6 and 12 months post‐surgery. We tested associations using Spearman's partial correlations and logistic regression analyses, adjusting for age, sex and body mass index. sICAM‐1 and VEGFD showed a significant positive correlation with cancer‐related fatigue at baseline and 6‐, and 12‐month follow‐up (sICAM‐1: r = 0.19, p = 0.010; r = 0.24, p = 0.004; r = 0.25, p = 0.006; VEGFD: r = 0.20, p = 0.006; r = 0.15, p = 0.06; r = 0.23, p = 0.01 respectively). Biomarkers of inflammation and angiogenesis measured prior to surgery are associated with cancer‐related fatigue in colorectal cancer patients throughout various time points. Our results suggest the involvement of overexpressed sICAM‐1 and VEGFD in the development of fatigue.